Genome description of Nostoc ellipsosporum strain NOK (Nostocales, Cyanobacteria) isolated from an arsenic contaminated paddy field of the Bengal Delta Plains. (3rd September 2021) - Ghosh, Anwesha; Bhadury, Punyasloke
Abstract: A diazotrophic cyanobacterium, Nostoc ellipsosporum strain NOK, was isolated from an arsenic contaminated paddy field of the Bengal Delta Plains (BDP). Located across India and Bangladesh, BDP, is one of the worst arsenic (As)-affected regions of the world. Previous studies have shown this isolate to be tolerant to high concentration of arsenic (≦400 μ M). The genome of this isolate was sequenced to identify the genes involved in various metabolic pathways including arsenic resistance and biofilm formation. Whole genome analyses showed Nostoc ellipsosporum strain NOK to be closely related to N. punctiforme strain PCC73102. The genome is about 10.9 Mbp which assembled into 694 contigs. Genome annotation identified 10120 genes out of which 10000 were CDSs. There are a total of 9927 protein coding genes in addition to 120 RNA coding genes. The genome codes three 5S rRNA, four 16S rRNA and three 23S rRNA genes along with 103 tRNAs, 7 ncRNAs and 73 pseudo-genes. The G + C% of the genome is 54.28. The genome codes for crucial genes involved in biofilm formation in response to stress conditions including arsenic stress. The ars BHC operon is present within the genome which makes this tolerant to high concentration of arsenic which might lead to biofilm formation. A number of ABC transporters including cys UW and sbp (sulfate/thiosulfate), nrt ABC (nitrate/nitrite/cyanate), cmp ABCD (bicarbonate), ssu ABC (alkane sulfonate), mod ABCF (molybdate; 2 copies), afu AC (iron), pst A (phosphate; 2 copies), pst BC, pst S (4 copies), cbi OQ (cobalt and nickel) and opu BC, opu BB and opu BA (osmoprotectants) were identified.